Helium identification with LHCb - Aaij, Roel; Bachmann, Sebastian; Caspary, Rowina; Carus, Leon; Cocha Toapaxi, Carlos; De Cian, Michel; Herrero Gascón, Paula; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kubat, Jakub; et al. (Journal of Instrumentation, 2024)
The identification of helium nuclei at LHCb is achieved using a method based on measurements of ionisation losses in the silicon sensors and timing measurements in the Outer Tracker drift tubes. The background from photon conversions is reduced using the RICH detectors and an isolation requirement. The method is developed using pp collision data at √(s) = 13 TeV recorded by the LHCb experiment in the years 2016 to 2018, corresponding to an integrated luminosity of 5.5 fb-1. A total of around 105 helium and antihelium candidates are identified with negligible background contamination. The helium identification efficiency is estimated to be approximately 50% with a corresponding background rejection rate of up to 𝒪(1012). These results demonstrate the feasibility of a rich programme of measurements of QCD and astrophysics interest involving light nuclei.
The LHCb Collaboration: R. Aaĳ, S. Bachmann, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, M. Schmelling, R. Skuza, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov [und 1075 weitere]
Gesehen am 11.11.2024